A comparative study of the faculty development programs of state universities - Buhay, Constancia Dupan 1914- ([Quezon City s.n.], 1974)
This study was conducted to determine the level of professional education of the instructional staffs of the Central Luzon State University (CLSU), Mindanao State University (MSU), Central Mindanao University (CMU), and the University of Eastern Philippines (UEP). Data gathered from laws, the University president's annual reports, and a questionnaire were interpreted in terms of averages, patterns, and deviations, and their implications to faculty development. MSU's faculty development program is the most advanced, upgrading 94 of its faculty in 1965-1972, followed by CMU (84), CLSU (66) and UEP (34).
Thesis (M.Ed.)--University of the Philippines.
Keywords: State universities and colleges -- Philippines; Universities and colleges -- Faculty